2020
DOI: 10.1111/1365-2745.13566
|View full text |Cite
|
Sign up to set email alerts
|

Climate influences the value of a plant structural defence against browsing

Abstract: 1. The circumstances that select for plant anti-herbivore defences are not well understood. In New Zealand, the 'divaricate' cage-like architecture of many woody plants may have arisen as a defence against avian browsing; it also has some ability to deter browsing by introduced deer. Its prominence on alluvial soils in frosty and droughty areas led us to hypothesize that structural defences are of most value where fertile soils coincide with climatic constraints that prevent plants from quickly growing out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…3) is compatible with an explanation based solely on climate (Diels, 1896;McGlone & Webb, 1981), other studies have implicated browsing in the evolution of cage architectures. Experiments have shown New Zealand divaricate plants to be less attractive to both avian and ungulate browsers than larger leaved, more sparselybranched relatives (Pollock et al, 2007;Lusk et al, 2021), as also seen with cage architectures in southern Africa (Charles-Dominique et al, 2017). These studies indicated a selective advantage of the divaricate habit and of cage architecture, in general, in deterring browsers.…”
Section: Discussionmentioning
confidence: 97%
“…3) is compatible with an explanation based solely on climate (Diels, 1896;McGlone & Webb, 1981), other studies have implicated browsing in the evolution of cage architectures. Experiments have shown New Zealand divaricate plants to be less attractive to both avian and ungulate browsers than larger leaved, more sparselybranched relatives (Pollock et al, 2007;Lusk et al, 2021), as also seen with cage architectures in southern Africa (Charles-Dominique et al, 2017). These studies indicated a selective advantage of the divaricate habit and of cage architecture, in general, in deterring browsers.…”
Section: Discussionmentioning
confidence: 97%
“…Island systems, such as New Zealand, often provide global precedents for long‐term, large‐scale management of ecosystems to biological invaders (Hulme, 2020; Peltzer et al, 2019; Simberloff, 2019). Because the introduction and establishment of invasive ungulates in New Zealand occurred largely over the last century, the impacts of invasive ungulates on New Zealand forests have been well documented, with ungulates causing local declines in highly palatable forest species in some types of forest shortly after introduction (Mark & Baylis, 1975), as well as ongoing shifts in both forest structure (Coomes, Allen, et al, 2003; Peltzer et al, 2014) and composition (Lusk et al, 2021). However, both ungulate abundance and impacts vary through time (Figure 1) and long‐term data are needed to determine their effects on long‐lived tree species and forest ecosystem properties, such as C sequestration (Wardle & Peltzer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Because these defences may have been costly to maintain (e.g. Lusk et al 2021), when large herbivores were absent the selective pressure to retain defensive adaptations may have decreased (e.g. Bowen & Vuren 1997).…”
Section: Introductionmentioning
confidence: 99%